Political Polarization and the Size of Government - Erik Lindqvist; Robert Östling (Research Institute of Industrial Economics (IFN), 2008)
We study the effect of political polarization on government spending and redistribution using the dispersion of self-reported political preferences as our measure of polarization. Politically polarized countries have lower levels of redistribution and government consumption. The relationship between political polarization and the size of government is stronger in democratic countries, indicating that the effect goes through the political system. The results are robust to a large set of controlvariables, including GDP per capita and income inequality.
Keywords: H11; H20; H41; 330; Political Polarization; Social Cohesion; Ethnic Fractionalization; Social Capital; Size of Government; Regierung; Öffentliche Verwaltung; Gesellschaftliches Bewusstsein; Politische Kultur; Politische Partei